Nivolumab in patients with advanced gastric or gastro-oesophageal junction cancer refractory to, or intolerant of, at least two previous chemotherapy regimens (ONO-4538-12, ATTRACTION-2): a randomised, double-blind, placebo-controlled, phase 3 trial. Issue 10111 (2nd December 2017) - Kang, Yoon-Koo; Boku, Narikazu; Satoh, Taroh; Ryu, Min-Hee; Chao, Yee; Kato, Ken; Chung, Hyun Cheol; Chen, Jen-Shi; Muro, Kei; Kang, Won Ki; Yeh, Kun-Huei; Yoshikawa, Takaki; et al.
Summary: Background: Patients with advanced gastric or gastro-oesophageal junction cancer refractory to, or intolerant of, two or more previous regimens of chemotherapy have a poor prognosis, and current guidelines do not recommend any specific treatments for these patients. We assessed the efficacy and safety of nivolumab, a fully human IgG4 monoclonal antibody inhibitor of programmed death-1 (PD-1), in patients with advanced gastric or gastro-oesophageal junction cancer who had been previously been treated with two or more chemotherapy regimens. Methods: In this randomised, double-blind, placebo-controlled, phase 3 trial done at 49 clinical sites in Japan, South Korea, and Taiwan, eligible patients (aged ≥20 years with unresectable advanced or recurrent gastric or gastro-oesophageal junction cancer refractory to, or intolerant of, standard therapy [including two or more previous chemotherapy regimens], with an Eastern Cooperative Oncology Group [ECOG] performance status of 0–1, and naive to anti-PD-1 therapy or other therapeutic antibodies and pharmacotherapies for the regulation of T cells) were recruited. Patients were randomly assigned (2:1) using an interactive web response system to receive 3 mg/kg nivolumab or placebo intravenously every 2 weeks, stratified by country, ECOG performance status, and number of organs with metastases. Study treatment was continued until progressive disease per investigator assessment or onset of toxicities requiring permanent discontinuation. Patients and investigators were masked to group assignment. The primary endpoint was overall survival in the intention-to-treat population. Safety was analysed in all patients who received at least one dose of study treatment. This study is ongoing but not recruiting new patients, and is registered withClinicalTrials.gov, numberNCT02267343 . Findings: Between Nov 4, 2014, and Feb 26, 2016, we randomly assigned 493 patients to receive nivolumab (n=330) or placebo (n=163). At the data cutoff (Aug 13, 2016), median follow-up in surviving patients was 8·87 months (IQR 6·57–12·37) in the nivolumab group and 8·59 months (5·65–11·37) in the placebo group. Median overall survival was 5·26 months (95% CI 4·60–6·37) in the nivolumab group and 4·14 months (3·42–4·86) in the placebo group (hazard ratio 0·63, 95% CI 0·51–0·78; p<0·0001). 12-month overall survival rates were 26·2% (95% CI 20·7–32·0) with nivolumab and 10·9% (6·2–17·0) with placebo. Grade 3 or 4 treatment-related adverse events occurred in 34 (10%) of 330 patients who received nivolumab and seven (4%) of 161 patients who received placebo; treatment-related adverse events led to death in five (2%) of 330 patients in the nivolumab group and two (1%) of 161 patients in the placebo group. No new safety signals were observed. Interpretation: In this phase 3 study, the survival benefits indicate that nivolumab might be a new treatment option for heavily pretreated patients with advanced gastric or gastro-oesophageal junction cancer. Ongoing trials that include non-Asian patients are investigating nivolumab for advanced gastric or gastro-oesophageal junction cancer in various settings and earlier treatment lines. Funding: Ono Pharmaceutical and Bristol-Myers Squibb.